(untitled) (Conferencea, 2023)
The academy is a unique cultural institution in ancient Chinese society, which integrates teaching and research, and has made a marked effect on the inheritance of civilization in the long history of Chinese education. Among them, academies in the Xinzhou area of Shanxi province, develop in the Ming Dynasty and prosper in the Qing Dynasty, advancing the evolution of education in Shanxi and even the entire country. This article takes Xinzhou regional academies from 1368 to 1840 as the research object, introduces the geography and humanities of this region in detail, excavates educational characteristics of regional academies, and objectively expounds their historical functions.